Early initiated feeding versus early reached target enteral nutrition in critically ill children: An observational study in paediatric intensive care units in Turkey. (26th December 2017) - Baǧci, Soyhan; Keleş, Elif; Girgin, Feyza; Yıldızdaş, Dinçer R; Horoz, Özden Ö; Yalındağ, Nilüfer; Tanyıldız, Murat; Bayrakçi, Benan; Kalkan, Gökhan; Akyıldız, Başak N; Köker, Alper; Köroğlu, Tolga; et al.
Abstract : Aim: Although early enteral nutrition (EN) is strongly associated with lower mortality in critically ill children, there is no consensus on the definition of early EN. The aim of this study was to evaluate our current practice supplying EN and to identify factors that affect both the initiation of feeding within 24 h after paediatric intensive care unit (PICU) admission and the adequate supply of EN in the first 48 h after PICU admission in critically ill children. Methods: We conducted a prospective, multicentre, observational study in nine PICUs in Turkey. Any kind of tube feeding commenced within 24 h of PICU admission was considered early initiated feeding (EIF). Patients who received more than 25% of the estimated energy requirement via enteral feeding within 48 h of PICU admission were considered to have early reached target EN (ERTEN). Results: Feeding was initiated in 47.4% of patients within 24 h after PICU admission. In many patients, initiation of feeding seems to have been delayed without an evidence‐based reason. ERTEN was achieved in 43 (45.3%) of 95 patients. Patients with EIF were significantly more likely to reach ERTEN. ERTEN was an independent significant predictor of mortality ( P  < 0.001), along with reached target enteral caloric intake on day 2 associated with decreased mortality. Conclusions: There is a substantial variability among clinicians' perceptions regarding indications for delay to initiate enteral feeding in critically ill children, especially after the first 6 h of PICU admission. ERTEN, but not EIF, is associated with a significantly lower mortality rate in critically ill children.